Low-Key Load-Bearing: Defining the National Role of Canada’s Library Publishing Programs - Betz, Sonya; Uhl, Emma; Nason, Mike (The Canadian Journal of Information and Library Science / La Revue canadienne des sciences de l’information et de bibliothéconomie)

(untitled) (Canadian Association for Information Science - Association canadienne des sciences de l'information, 2025)
Canadian academic libraries play a demonstrably load-bearing yet under-recognized role in the nation’s scholarly publishing ecosystem, supporting a predominantly independent, non-commercial journal landscape. While global trends reveal an oligopoly of large commercial publishers, Canadian publishing remains defined by diversity, with libraries offering essential infrastructure and services for journals rooted in open access and equity. This study explores the scope and nature of library publishing services in Canada, analyzing data from 42 institutions to reveal significant contributions to the production, dissemination, and preservation of scholarly knowledge. Despite limited resources, these programs provide critical support for diamond open access publishing models, bibliodiversity, and underserved journal types. As national and international conversations on scholarly publishing evolve, it is vital to recognize libraries not just as contributors, but as key players driving a more equitable and sustainable publishing system.